Reprogramming energy homeostasis in children with overweight through cognitive training and social interaction. A study protocol to estimate leptin sensitivity - Russo, Valentina; Menghini, Deny; Mainardi, Marco; Fintini, Danilo; Aureli, Alessia; Gianni, Nicoletta; Ravà, Lucilla; Rea, Maria Alessia; Scozia, Gabriele; Spiezia, Chiara; Scabia, Gaia; Furini, Giulia; et al. (Frontiers in Endocrinology, 2025)
Leptin is a hormone secreted by adipocytes in proportion to the size of adipose tissue. By acting on its receptor, LepRb, primarily expressed in the hypothalamus, leptin promotes a negative energy balance by strongly suppressing appetite and stimulating energy expenditure. The majority of patients with obesity exhibit elevated leptin production, indicating that leptin becomes ineffective in regulating energy balance in this context. In the growing child, leptin modulates synaptic plasticity and thus leptin resistance may exert a key role in neurodevelopment. So far, studies in humans have investigated leptin secretion but not leptin resistance. We designed a research protocol (RESILIENT project) to study leptin sensitivity in vivo and ex vivo in growing children (6 to 11 years of age), and its association with neurodevelopmental features. The project will investigate the additive effects of Cognitive Training (CT) and Social Training (ST) on leptin sensitivity, compared to stand-alone Intensive Health Behaviour Treatment (IHBT) in children with obesity or overweight. In vivo investigation of leptin sensitivity may be particularly important for providing evidence of the metabolic and cognitive effects necessary for developing novel anti-obesity treatments.Clinical trial registrationhttps://clinicaltrials.gov/study/, identifier NCT06931730.